Pengaruh likuiditas, profitabilitas, dan manajemen laba terhadap nilai perusahaan: Peran moderasi kepemilikan manajerial pada perusahaan sektor infrastruktur - Saputri, Eko Dewi; Pratiwi, Desy Nur; Rukmini, Rukmini (Journal of Accounting and Digital Finance, 2023)
The main objective of these findings is to assess how Liquidity, Profitability Ratios and Profit Management influence the value of infrastructure sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. Also, the role of managerial ownership as a moderating factor in this relationship should be examined. This research focuses on a sample of 10 infrastructure group companies selected using purposive sampling, resulting in a sample size of 50. Data collection resulted in extracting information from financial reports available on the official website of the Indonesia Stock Exchange. The analysis uses multiple linear regression. The research results found that liquidity hurts company value. Apart from that, profitability has a substantial positive effect on company value. However, earnings management does not have a significant impact on company value. Other results show that managerial ownership cannot moderate the relationship between liquidity and company value, profitability and company value, as well as profit management and company value.